The effect of an angiotensin converting enzyme inhibitor on intestinal wound healing - Ilhan, YS; Bulbuller, N; Kirkil, C; Ozercan, R; Seckin, D (Academic Press Inc Elsevier Science, 2005)
Background. Dehiscence of intestinal anastomosis is associated with high mortality and morbidity rates. Angiotensin II is a potent agent in the acceleration of wound repair. Angiotensin converting enzyme (ACE) inhibitors have antifibrogenic effects. Aim. This study was performed to investigate the effect of ACE inhibitors on healing of intestinal anastomosis. Materials and methods. Forty-five male Wistar albino rats were divided into three groups. Ileum was divided above 10 cm from ileocecal valve after laparotomy and a single-layer ileoileal anastomosis was performed. While no treatment was given to rats in group 1, Lisinopril (an ACE inhibitor) was given to rats in group 2 and group 3 for post-operative 7 days in drinking water at 50 and 5 mg/I concentrations, respectively. Estimated amounts of supplied lisinopril were 6.5 and 0.65 mg/kg/day in groups. On post-operative 8th day, relaparotomy was performed and anastomosis-bursting pressures were measured. Then blood and tissue samples were taken for serum transforming growth factor beta-1 and tissue hydroxyproline measurements and histopathological examinations. Results. High dose of lisinopril impaired the all parameters of anastomotic wound healing including bursting pressure, tissue hydoxyproline level, collagen deposition and epithelization (P < 0.001, group 2 versus groups 1 and 3). But low dose of lisinopril had no effect on those parameters (P > 0.05, group 1 versus group 3). Conclusion. It was concluded that lisinopril has impaired intestinal wound healing in a dose dependent manner and low doses of lisinopril can be safely used on patients with intestinal anastomosis. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: angiotensin converting enzyme inhibitor; lisinopril; transforming growth factor; intestinal anastomosis; wound healing